Pool Toes: A Case Report - Mohammad Munshi; Luca Borradori; Nikhil Yawalkar; Kristine Heidemeyer (Karger Publishers, 2023)
Pool toes, a sport-related dermatosis, are caused by mechanical friction and water exposure, resulting in a special variant of irritant contact dermatitis. It is common in children, often misdiagnosed, and rarely reported. Here we report a case of a 7-year-old girl who developed this unusual type of frictional dermatitis; a pool toes diagnosis has been made. With topical corticosteroids, favorable results have been achieved. The recovery and healing process will be facilitated if one is aware of the underlying causes of such dermatitis and ceases the triggering factors.